STRATEGI PENINGKATAN PENDAPATAN RETRIBUSI DAERAH DI KOTA KENDARI - Jamal Bake; Muh. Yusuf; Akbar Wahbi (Journal Publicuho, 2022)
One source of local revenue that has the potential to be developed to support regional fiscal capacity is revenue from regional levies. The purpose of this writing is to find out the strategy for increasing regional retribution revenue in Kendari City, Southeast Sulawesi Province. The results of the study found that the intensification strategy through improving the quality of public services and reforming the collection system, improving the quality of management staff, using technology, and increasing supervision, as well as the extensification strategy through updating rules, creating new regulations and establishing new sources of fees as well as increasing citizen awareness in Paying user fees is a strategy of the Kendari City government in an effort to increase local revenue.